Do progestins contribute to (anti-)androgenic activities in aquatic environments? - Šauer, Pavel; Bořík, Adam; Golovko, Oksana; Grabic, Roman; Staňová, Andrea Vojs; Valentová, Olga; Stará, Alžběta; Šandová, Marie; Kocour Kroupová, Hana (Environmental pollution (Barking, Essex, 2018)
Unknown compounds with (anti-)androgenic activities enter the aquatic environment via municipal wastewater treatment plants (WWTPs). Progestins are well-known environmental contaminants capable of interfering with androgen receptor (AR) signaling pathway. The aim of the present study was to determine if 15 selected progestins have potential to contribute to (anti-)androgenic activities in municipal wastewaters and the respective recipient surface waters. AR-specific Chemically Activated LUciferase gene eXpression bioassay in agonistic (AR-CALUX) and antagonistic (anti-AR-CALUX) modes and liquid chromatography tandem atmospheric pressure chemical ionization/atmospheric photoionization with hybrid quadrupole/orbital trap mass spectrometry operated in high resolution product scan mode (LC-APCI/APPI-HRPS) methods were used to assess (anti-)androgenic activity and to detect the target compounds, respectively. The contribution of progestins to (anti-)androgenic activities was evaluated by means of a biologically and chemically derived toxicity equivalent approach. Androgenic (0.08-59 ng/L dihydrotestosterone equivalents - DHT EQs) and anti-androgenic (2.4-26 μg/L flutamide equivalents - FLU EQs) activities and progestins (0.19-75 ng/L) were detected in selected aquatic environments. Progestins displayed androgenic potencies (0.01-0.22 fold of dihydrotestosterone) and strong anti-androgenic potencies (9-62 fold of flutamide). Although they accounted to some extent for androgenic (0.3-29%) and anti-androgenic (4.6-27%) activities in influents, the progestins' contribution to (anti-)androgenic activities was negligible (≤2.1%) in effluents and surface waters. We also tested joint effect of equimolar mixtures of target compounds and the results indicate that compounds interact in an additive manner. Even if progestins possess relatively strong (anti-)androgenic activities, when considering their low concentrations (sub-ng/L to ng/L) it seems unlikely that they would be the drivers of (anti-)androgenic effects in Czech aquatic environments.
Keywords: chemické látky znečišťující vodu; Target analysis; progestiny; Androgens; antagonisté androgenů; Androgen Antagonists; odpadní voda; Water Pollutants, Chemical; Biological Assay; Waste Water; Sample acidification; Solid-phase extraction; Progestagens; androgeny; Wastewater; biotest; Progestins